Respiratory antibacterial prescribing in primary care and the COVID-19 pandemic in England, winter season 2020–21. (13th December 2021) - Andrews, Amelia; Bou-Antoun, Sabine; Guy, Rebecca; Brown, Colin S; Hopkins, Susan; Gerver, Sarah
Abstract: Background: Antibacterial prescribing for respiratory tract infections (RTIs) accounts for almost half of all prescribing in primary care. Nearly a quarter of antibacterial prescribing in primary care is estimated to be inappropriate, the greatest being for RTIs. The COVID-19 pandemic has changed the provision of healthcare services and impacted the levels of antibacterials prescribed. Objectives: To describe the changes in community antibacterial prescribing for RTIs in winter 2020–21 in England. Methods: RTI antibacterial prescribing was measured in prescription items/1000 population for primary care from January 2014 and in DDDs/1000 population/day for the totality of RTI prescribing [combined with Accident & Emergency (A&E) in secondary care], from January 2016 to February 2021. Trends were assessed using negative binomial regression and seasonally adjusted interrupted time-series analysis. Results: Antibacterials prescribed for RTIs reduced by a further 12.4% per season compared with pre-COVID ( P <  0.001). In winter 2020–21, RTI prescriptions almost halved compared with the previous winter in 2019–20 ( P <  0.001). The trend observed for total RTI prescribing (primary care with A&E) was similar to that observed in the community alone. Conclusions: During COVID-19, RTI prescribing reduced in the community and the expected rise in winter was not seen in 2020–21. We found no evidence that RTI prescribing shifted from primary care to A&E in secondary care. The most likely explanation is a decrease in RTIs and presentations to primary care associated with national prevention measures for COVID-19.